The Influence of Mother’s Personality and Social Support on Emotional Socialization of Working Mother in Rural Family - Damara Liana Hermawan; Alfiasari - Alfiasari (Department of Family and Consumer Sciences, Bogor Agricultural University, 2017)
The aim of this research was to analyze the influence of mother’s personality and social support on emotional socialization of working mother in rural family. This research was conducted at Ciampea Sub District, Bogor Regency. Design of this research was cross sectional study. The population of this research were working mothers from rural family who had teenager from four chosen junior high schools. The samples consist of 80 working mothers that were chosen by purposive sampling. Result showed that the higher scorees of extraversion and openness of mother’s personality, the higher emotional socialization that was conducted by mother to her teenager. Moreover, openness of mother’s personality consistenly influence on emotional socialization. This result showed that there is a mother’s personality roles toward emotional socialization that conducted by mother to her teenager. This research was not found correlation between social support and emotional socialization.